The soundscape of the ceremonies held for the beatification of St Teresa of Ávila in the Crown of Aragon, 1614. - KNIGHTON, TESS; MAZUELA-ANGUITA, ASCENSIÓN (Scripta)
The beatification of Saint Teresa of Ávila in October 1614 gave rise to widespread celebrations in many of the cities and towns of the Iberian Peninsula. Printed relaciones describing these celebrations, despite their limitations --in terms of political agenda, propaganda, rivalry and literary style-- can nevertheless provide information about musical experience and can help to recreate the ephemeral soundscapes of these events. This article will focus on the ceremonies held in the Crown of Aragon, especially Saragossa and Barcelona, taking into consideration the typology of different musics --heraldic, divine and festive-- and factors such as the moment in time, function, dynamic, urban spaces and blurring of boundaries, public (listeners), musical resources and performance practice, repertories and genres, signifiers and associations for listeners, and impact.